Toxoplasmose: Perfil Sorológico em gestantes atendidas em Postos de Saúde do Município de Pelotas-RS - Cademartori, Beatris Gonzalez (2007)
The toxoplasmosis acquired during pregnancy of benign course in imunocompetentes patients and asymptomatic in 85% of the cases may infect the fetus and result in congenital infection. Although most of the newborns do not present symptoms or clinical signs, there may be sequelae during the childhood and adult life, being the corioretinitis the most frequent one. Among the strategies to prevent congenital toxoplasmosis we can find the education for health and the preconception trial, which aim is to reduce the exposition to the risk factors that may lead to an infection by T. gondii, to detect and to treat acute infection in pregnant woman. The aims of this study were to evaluate the prevalence and risk of congenital transmission by Toxoplasma gondii, through serological analysis of the pregnant women and also through their knowledge about the zoonose transmission routes, to check the possible association between the soropositivity of the pregnant women and their exposition to the infection risk factors, and also to compare the Chemiluminescence and Indirect Immunofluorescence techniques in the diagnosis of the toxoplasmosis in the studied sample. A transversal study was conducted, with 425 pregnant women who were attending prenatal care in public health centres of Pelotas (RS-Brazil), during the period of May to November 2006. It was verified a T. gondii soroprevalence of (IgG) 54,8% and it was not detected the presence of IgM antibodies. The analysis of the risk factors showed a significant association (p<0.05) between the soropositivity of the pregnant women and their age, the handle of raw meat, the intake of raw vegetables, raw or undercooked meat and raw or nonpasteurized milk and direct contact with the soil. The Logistic Regression Model confirmed the above associations to the intake of raw or undercooked meat (OR=1.85) and to the direct contact with the soil (OR=2.67). The interaction with cats did not present a significant association with the T. gondii soropositivity patients. It was observed that the pregnant women who were interviewed did not know much about the disease and its main sources of infection. The Chemiluminescence technique proved to be an adequate one in the routine diagnosis of the T. gondii infection as, besides being a practical technique, it showed results comparable to the ones of the Indirect Immunofluoresence, sensibility, specificity and accuracy. The results indicate the necessity of implementing T. gondii primary prevention programmes for the pregnant women who as a way of reducing the risks of congenital toxoplasmosis.